Assessment of the contributions of contract farming on alleviating financial capital constraints of rural farm households in Tanzania: A case of tanseed international LTD - Msovu, Safiel Fahamuel (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for award of the Degree of Master of Science in Accounting and Finance of Mzumbe University.